Agro-Morphological Evaluation of Hybrid Maize (Zea mays) in the Subtropical Region of Nepal - Aayushma Shrestha; Bijay Mahato; Pratik Gurung (AgroEnvironmental Sustainability)
Agro-morphological characterization is crucial to evaluate the performance of maize hybrids on the basis of various traits and to identify superior hybrids with desirable features. The objective of this research was to identify the superior maize hybrid based on field performance. A total of thirteen maize hybrids were evaluated in a randomized complete block design with three replications at Sharanamati, Jhapa, Nepal during March-July, 2024. All the data except grain yield was recorded from five sample plants in each plot where grain yield was recorded from the whole plot and statistical analysis was done using R-studio. The results revealed that Superking-4455 is more appropriate for areas with shorter growing seasons since it generally flowers sooner in comparison to other genotypes such as INH-5619 and RH-6. Shorter plants like PAC-7202309 were found to be more resistant to lodging and are preferred in certain regions where wind or heavy rains are common over tall varieties like Star-56. The maximum grain yield was 10.09 t/ha which was achieved by Star-56, closely followed by Superking-4455 and RH-6 whose yield was 9.67 t/ha and 9.54 t/ha respectively. PAC-7202309 produced the lowest yield which was 4.49 t/ha, most likely as a result of its low TGW, NOP, and NOC. The results suggested that, while low-performing genotypes like PAC-7202309 need more research or breeding and agronomic methods to improve their performance, high-performing genotypes like RH-6, Star-56, and Superking-4455 are excellent possibilities for enhancing maize output in Saranamati, Jhapa.